In situ conservation and use of crop wild relatives in three ACP countries of the Southern African Development Community (SADC) region - Bioversity International; University of Birmingham; University of Mauritius; Department of Agriculture, Forestry and Fisheries; Zambia Agriculture Research Institute (Bioversity International, 2016)
The leaflet provides a summary of the major results of the project: In Situ Conservation and Use of Crop Wild Relatives in three ACP countries of the Southern African Development Community (SADC) region (2014 - 2016), which was implemented in Mauritius, South Africa and Zambia.